2020
DOI: 10.1042/bsr20200435
|View full text |Cite
|
Sign up to set email alerts
|

The cellular expression and proteolytic processing of the amyloid precursor protein is independent of TDP-43

Abstract: Alzheimer’s disease (AD) is a neurodegenerative condition, of which one of the cardinal pathological hallmarks is the extracellular accumulation of amyloid β (Aβ) peptides. These peptides are generated via proteolysis of the amyloid precursor protein (APP), in a manner dependent on the β-secretase, BACE1 and the multicomponent γ-secretase complex. Recent data also suggest a contributory role in AD of transactive response DNA binding protein 43 (TDP-43). There is little insight into a possible mechanism linking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(35 reference statements)
2
3
0
Order By: Relevance
“…After APP proteolysis, AICD is translocated to the nucleus by binding to adaptor Fe65 and regulates gene transcription [ 49 , 65 ]. Consistent with previous findings [ 20 , 59 ], AICD immunoreactivity recognized by an AICD-specific antibody was mainly observed in the nucleus. Notably, knockout of CHCHD6 in HT-22 cells greatly enhanced the intensity of AICD in the nucleus (Fig.…”
Section: Resultssupporting
confidence: 93%
“…After APP proteolysis, AICD is translocated to the nucleus by binding to adaptor Fe65 and regulates gene transcription [ 49 , 65 ]. Consistent with previous findings [ 20 , 59 ], AICD immunoreactivity recognized by an AICD-specific antibody was mainly observed in the nucleus. Notably, knockout of CHCHD6 in HT-22 cells greatly enhanced the intensity of AICD in the nucleus (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Perhaps, in our work, we observe the AICD localization in the nucleolus being more dense than in surrounding karyoplasm. This corresponds to the recent study by Hicks et al, where the predominant localization of AICD in neuron cell nucleolus was shown 42,43 .…”
Section: Discussionsupporting
confidence: 91%
“…We suggest that this is C-terminal AICD fragment, because full-size APP is not expected to enter the nucleus. Recent studies have shown that full-size APP is localized in perikaryon without entering the nucleus 42,43 . However, there are data on interaction and formation of relatively stable APP or APP fragment, exceeding AICD, with Tip60, Fe65, and Pat1a, which is further probably translocated into the nuclear area.…”
Section: Discussionmentioning
confidence: 99%
“…Data associating TDP-43 with diffuse A pathology irrespective of tau is not reported and indeed, a study examining TDP-43 pathological correlates with antemortem A found no association with global amyloid PET signal 81 . In experimental systems, in vitro TDP-43 does not modulate the expression of APP, nor does APP affect TDP-43 expression 82 , but TDP-43 can accelerate Aβ aggregation in an in vitro seeding assay 83 . In a separate study, injection of TDP-43 into brains of a transgenic mouse model of AD β-amyloidosis altered β-amyloid assembly and increased accumulation of toxic β-Disease Models & Mechanisms • DMM • Accepted manuscript amyloid oligomers 84 .…”
Section: The Synergistic Relationship Between Tau and Tdp-43 Is Specificmentioning
confidence: 97%